The impact of microbiological consortia of autochthonous and allochthonous microorganisms on the parameters of wastewater treatment from car washes - Mazur, Robert; Włodyka-Bergier, Agnieszka; Kowalewski, Zbigniew; Kaszycki, Paweł; Starzec, Katarzyna (Instal, 2023)
Microbiological biopreparations as biotechnological methods support wastewater treatment processes. Unfortunately, in conditions with a short hydraulic retention time (up to 22 hours) in wastewater treatment plants, biological treatment processes are not able to effectively reduce the concentrations of COD, BOD5, and nutrients in the sewage. The authors tested both biopreparations with consortia of autochthonous and allochthonous microorganisms, and in both cases, no significantly significant differences in treatment efficiency were found compared to the control group (without the addition of biopreparations).